Penerapan Cognitive Behavior Therapy (CBT) untuk Meningkatkan Kematangan Hubungan Teman Sebaya melalui Pengembangan Rasa Percaya Diri - Ade Mutia; Bunga Ria Dini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Low self-confidence can hinder students’ ability to form relationships with their peers. This article aims to describe the application of Cognitive Behavioral Therapy (CBT) to enhance peer relationship maturity by developing self-confidence among students at SMK Negeri 2 Binjai. The method used was a case study with a descriptive approach. Data were collected through observation and interviews during individual counseling sessions with a 10th-grade student in the Machining Technology program who struggled to interact with peers due to feelings of inferiority stemming from his family’s economic circumstances. The results of the counseling indicated that the application of CBT helped the student transform negative thought patterns into more rational ones, thereby increasing his self-confidence. These changes led to increased courage in social interactions, improved adaptability, and better quality relationships with peers. Thus, CBT can serve as an effective approach in helping students develop self-confidence and more positive social relationships.